Didactic Audiovisual Translation and Foreign Language Education - TALAVAN, NOA (Routledge Research in Audiovisual Translation, 2024)
Didactic AVT; AVT; audiovisual translation; didactic audiovisual translation; Foreign language education; Media accessibility; Language and education; Noa Talaván; Jennifer Lertola; Alberto Fernández-Costales